Information technologies and the road to european integration - Pashchenko, О. А.; Terkhanova, О.V.; Medvedovska, Т. Р. (My University, 2024)
The role of information technologies in shaping global narratives is a multifaceted and significant aspect of the modern world. The media, as a primary vehicle for disseminating information, plays a crucial role in influencing political and socio-economic narratives. Information technologies have transformed the way narratives are constructed and distributed, impacting the identity and interests of global actors. This transformational impact has led to the emergence of a new digital economy, where businesses predominantly operate online, fostering new markets, collaboration, and communication. The growth of the digital economy has introduced fresh prospects for businesses and individuals, while also presenting new obstacles.
Keywords: інформаційні технології; європейська інтеграція; information technologies; European integration